ANALISIS PENYEBAB BELUM TERLAKSANANYA SISTEM KOMPUTERISASI DI TEMPAT PENDAFTARAN PASIEN RAWAT JALAN (TPPRJ) DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PEKANBARU TAHUN 2015 - Nur Maimun; Fitriani Astika (Sistem Informasi, 2016)
Computers as an electronic gear go through data, able to receive advice and output, the data is the as a high, precision, And the ability keep instructions to solve the problem. This study attempts to find out the cause of unrealized a computerized system in place registration ambulatory in RSUD Petala Bumi pekanbaru years 2015. Research methodology with a qualitative approach. technics data collection by means of observation, interviews and documentation. Data analysis qualitative analysis. The results of the study because the hospital new this year become the house district general hospital while first still in under UPT provincial health office riau. Human resources in components of the system computerized not enough. Facilities and infrastructure for a computerized system there has been no. There is no sop to a computerized system, and funding of the have been over budgeted but still in the process. In suggest: the sum of human resources in addition, make facilities and infrastructure, sop at the record medical and needs to be improved again efforts advocacy that ususlan budget / cost to a computerized systemin TPPRJ can be processed by related parties.